From I to we: participants' accounts of the development and impact of shared identity at large-scale displays of Irish national identity. Issue 1 (2nd January 2021) - Blaylock, Danielle L.; Stevenson, Clifford; O'Donnell, Aisling T.; Reicher, Stephen D.; Bryan, Dominic; Neville, Fergus G.; Muldoon, Orla T.
ABSTRACT: In Ireland, ritual events and parades have been a central part of civic and public life. However, there is limited understanding of the identity processes at work at these collective events. The present research aims to examine how participants attending collective events come to recognise shared social identification and the impact that this awareness is reported to have on intragroup processes. Interview data were collected over the course of two years at the St Patrick's Day parade and 1916 Easter Rising commemorations in Dublin and Belfast with both participants and attendees at the events. Thematic analysis revealed that to the extent that individuals saw the event as an identity event, they used attendance as their primary indication of shared identity, along with visual identity markers, shared experiences, and shared affects. Participants' accounts of the experience of shared identity focused upon a range of cognitive, affective, and social variables which together suggested a relational transformation in the crowd. These findings suggest that shared identity is an emergent state which plays a critical role in transforming social relations within the collective.